PEMANFAATAN LIMBAH INDUSTRI BATU APUNG UNTUK PEMBUATAN BATU HIAS BANGUNAN - Arifin Hargianto; Iman Satyarno; Mudjijana - (ASEAN Journal of Systems Engineering, 2013)
Mining and processing activities have caused pumice deposits of waste. Waste from industrial processing of pumice is used as an innovation to increase the value of the waste and then profits will be obtained. One of the examples is making them as decorative stones.Raw materials used in this study are industrial waste pumice from Lombok, with the size less than 2 cm. The machine used as a fine aggregate pumice waste destruction is a crusher. Variations of the composition of the mixed mortar are made from white cement, powdered pumice waste as fine aggregate, and water. Variation is the comparison between the composition of the mixture of white portland cement (pc) and fine aggregate from pumice waste (Ag.h) with comparisons 1Pc: 2Ag.h, 1Pc: 4Ag.h, 1Pc: 6Ag.h, 1Pc: 8Ag.h and 1Pc: 10Ag.h. Tests are conducted to determine the characteristics of fine aggregate made from pumice waste, while the mortar test includes compressive strength, flexural strength, specific gravity and water absorption.The results show that the fine aggregate made from pumice industrial waste materials has the following characteristics : modulus of fine grains is 2.61, specific gravity is 1.67, absorption of water is 23.08%, mud content is 26.10%, and weight lose unit is 0.537 gr/cm3. On the mortar test, mixed variations affect the compressive strength, flexural strength, specific gravity and water absorption. The test results find that the variation of a mixture of 1 pc: 2 Ag.h has characteristics of natural stone that is the closest to the gravity of 262 gr/cm and with 3,11 813 MPa in compressive strength, 0344 MPa in flexural strength, and 19.93% in water absorption value. Variation of a mixture of 1 pc: 2 Ag.h has also been tested in the manufacture of decorative stones and the results can have the similar look with the natural stone.